2020
DOI: 10.3390/antibiotics9080439
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Levofloxacin and Moxifloxacin in Select Hospitals in Uganda: A Pilot Study to Assess Guideline Concordance

Abstract: Background: In Uganda, national tuberculosis (TB) treatment guidelines were revised to include the newer generation fluoroquinolones among the second-line treatment options for multidrug-resistant TB. This study was designed to analyze if the prescription of these quinolones is compliant with country recommendations. Methods: This was an observational retrospective study of consumption data for 2017 and 2018 across four selected regional referral hospitals. The sources of consumption data were hospital pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The findings obtained through our contextualised AMS checklist mirror the published AMS reports in LMICs, which highlight the presence of national antimicrobial prescribing guidelines in the countries where the sites are located [ 21 , 31 , 32 , 33 ] but identify the challenges in AMR-specific education and training, diagnostic facilities, regulation of safety and efficacy of medications, and shortages of healthcare personnel and expertise [ 34 , 35 , 36 , 37 ]. Although these studies highlight the overall gaps in AMS implementation in LMICs, the differences observed across the regions, hospitals, and sites also demonstrate the need for case-by-case evaluations of AMS programmes for the development of appropriate and sustainable solutions.…”
Section: Discussionsupporting
confidence: 60%
“…The findings obtained through our contextualised AMS checklist mirror the published AMS reports in LMICs, which highlight the presence of national antimicrobial prescribing guidelines in the countries where the sites are located [ 21 , 31 , 32 , 33 ] but identify the challenges in AMR-specific education and training, diagnostic facilities, regulation of safety and efficacy of medications, and shortages of healthcare personnel and expertise [ 34 , 35 , 36 , 37 ]. Although these studies highlight the overall gaps in AMS implementation in LMICs, the differences observed across the regions, hospitals, and sites also demonstrate the need for case-by-case evaluations of AMS programmes for the development of appropriate and sustainable solutions.…”
Section: Discussionsupporting
confidence: 60%
“…The ndings obtained through our contextualised AMS checklist mirror published AMS reports in LMICs, which highlight the presence of national antimicrobial prescribing guidelines in the countries where the sites are located [21][22][23][24] but identify challenges in AMR-speci c education and training, diagnostic facilities, regulation of safety and e cacy of medications and shortages of healthcare personnel and expertise [25][26][27][28]. Although these studies highlight overall gaps in AMS implementation in LMICs, the differences observed across regions, hospitals and sites also demonstrate the need for case-by-case evaluations of AMS programmes for the development of appropriate and sustainable solutions.…”
Section: Ams Checklist Implementationsupporting
confidence: 61%
“…Many factors could contribute to the low adherence to the Uganda Clinical Guidelines, including poor dissemination of the guidelines, lack of proper diagnostic stewardship in hospitals, such as in microbiology and radiology, and long turnaround times for laboratory results. Lastly, in many settings, prescriber preferences and behaviors are a major cause for non-adherence to the guidelines [ 49 ]. Similar factors have been described elsewhere as barriers to guideline adherence [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%